STUDI ETNO-ORNITOLOGI BURUNG SEBAGAI BENTUK KEARIFAN LOKAL MASYARAKAT DI DESA PEMATANG GADUNG KABUPATEN KETAPANG - Silviyanti, Novia; Nurdjali, Bachrun; Kartikawati, Siti Masitoh (Universitas Tanjungpura, 2016)
Ethno-ornithology utilized to document traditional knowledge of the community, who have used the services of various bird species to support life, for example as a source of food, traditional medicine, traditional rituals, crafts, religious, and social life. The research objective is to explore forms of local wisdom relating to bird and bird species used to know the community and has values ​​of local wisdom in Pematang Gadung’s Village Ketapang. Based on the results of the study found as many as 45 species of birds as a form of local wisdom, classified into 22 families (family), 18 species of birds included in the protected category under the Act, CITES and IUCN. Only 28 species were found at the time of observation. Based on usability, quality value that is most widely used as a myth, while the little used that as a result of analysis using indicator. Cultural Values ​​Index, the highest cultural values ​​derived from species that have become a kind of domestication is Gallus domesticus (Gallus sp) with a score of 60 and score value ICS 3, while the value of the lowest cultural interests acquired from bird species Ixobrychus cinnamomeus value cultural interests 0.25 which means to have a score of 1. Key Words : Bird, etno-ornithology and local wisdom